Reaction kinetics of hydrothermal carbonization of loblolly pine - Reza, M. Toufiq; Yan, Wei; Uddin, M. Helal; Lynam, Joan G.; Hoekman, S. Kent; Coronella, Charles J.; Vásquez, Victor R. (Bioresource technology, 2013)
•An innovative reactor was designed to measure hydrothermal reaction kinetics.•At temperatures between 200 and 260°C, weight loss kinetics are quite rapid.•Reactions are modeled by parallel first-order degradation of hemicellulose and cellulose.•Mass transfer and reaction kinetics may both be important. Hydrothermal carbonization (HTC) is a pretreatment process to convert diverse feedstocks to homogeneous energy-dense solid fuels. Understanding of reaction kinetics is necessary for reactor design and optimization. In this study, the reaction kinetics and effects of particle size on HTC were investigated. Experiments were conducted in a novel two-chamber reactor maintaining isothermal conditions for 15s to 30min reaction times. Loblolly pine was treated at 200, 230, and 260°C. During the first few minutes of reaction, the solid-product mass yield decreases rapidly while the calorific value increases rapidly. A simple reaction mechanism is proposed and validated, in which both hemicellulose and cellulose degrade in parallel first-order reactions. Activation energy of hemicellulose and cellulose degradation were determined to be 30 and 73kJ/mol, respectively. For short HTC times, both reaction and diffusion effects were observed.